Ecological Impact of Compaction under Teak Plantation in the Foothill of Darjeeling Himalaya - Ram, Nirmal; Jana, M. M. (Indian Forester, 1997)
Ecological study under Teak plantation of 1968 in the foothill of Darjeeling Himalayas reveals that due to compaction of forest floor, decrease in height, diameter and basal area of Teak trees were in order of 8.3, 16.4 and 34.7 percent respectively. It may be due to less porosity and much bulk density of the soil. Due to compaction of the forest floor, species density of the undergrowth was 121.93% more than controlled area. Whereas species diversity was 68.30% less than controlled forest floor. Compactin leads presence of Paspalum sanguinalle and Oplismenus burmannii grasses having their value of 69.47 and 21.56 density/m2 whereas their presence in controlled forest floor were 21.14 and 4.80 respectively. So, result indicates that grasses are compaction resistants under controlled forest floor. Correa bengalensis a shrub represents 75% of its distribution. From compacted forest floor undergrowth biomass production was 1.150 ton/ha and from controlled floor, it was 2.584 ton/ha. So decrease of undergrowth production from compacted forest floor was 124.69 percent. Result also indicates that in compacted forest floor, fodder quantity was 1152.94 percent more than miscellaneous undergrowth biomass production. So, the result indicates that due to compaction of Teak plantation, productivity of Teak trees and its undergrowth decreases. This may be due to less porosity and much bullk density of the soils which has direct link with intake of water. Any biological activities under forest floor should be avoided for conservation of soils and water for better productivity point of view.